Влияние угла наклона главной режущей кромки на силу резания при глубоком сверлении литейних алюминиев - Маршуба, Вячеслав Павлович (НТУ "ХПИ", 2002)
The influence of the inconstant value of the angle of aerial of the main cutting edge of the standard drill with the elements of metal shavings dot the feat that the cutting edge is accomplished as a radius that’s with a diffract angle of arrival that differs from the generally accepted form of the dwindling. In the combination ninth the drinking of the tooth on the back surface, the inconstant wale of the angle of arrival of main cutting edge decrease the cutting force. It is caused by the fact the part of the cutting force at the deep drilling is directed on the removing of metal shavings out of the cutting zone. Therefore this drinking of the instrument let decrease the growth of the force be destroying of the continuous currents of shavings on stall harts that you can easier remove from the cutting zone.
Keywords: обработка механическая; стружка; момент крутящий